IR SPECTRA OF THIN FILMS OF CRYOVACUUM CONDENSATES OF ETHANOL - Aldiyarov, A.U. (Recent Contributions to Physics, 2008)
IR-spectrometric studies of structural-phase transformations in thin films of cryovacuum ethanol condensates have been carried out. The measurements were carried out in the temperature range from 12 K to 150 K. Changes in the nature of the vibrational spectra are interpreted as a result of structural thermally stimulated transformations in solid ethanol.